Protective Effects of Quercetin on Rat Pial Microvascular Changes during Transient Bilateral Common Carotid Artery Occlusion and Reperfusion - Lapi, Dominga; Vagnani, Sabrina; Pignataro, Giuseppe; Esposito, Elga; Paterni, Marco; Colantuoni, Antonio (Frontiers in Physiology, 2012)
The aim of this study was to assess the in vivo effects of quercetin on pial microvascular responses during transient bilateral common carotid artery occlusion (BCCAO) and reperfusion. Rat pial microcirculation was visualized by fluorescence microscopy through a closed cranial window. Pial arterioles were classified in five orders of branchings. Capillaries were assigned order 0, the smallest arterioles order 1 and the largest ones order 5. In ischemic rats, 30 min BCCAO and 60 min reperfusion caused arteriolar diameter decrease (by 14.5 ± 3.3% of baseline in order 2), microvascular leakage (0.47 ± 0.04 NGL: Normalized Grey Levels), leukocyte adhesion in venules (9 ± 2/100 µm venular length, v.l./30s) and reduction of capillary perfusion (by 40 ± 7% of baseline). Moreover, at the end of BCCAO and reperfusion there was a significant increase in reactive oxygen species formation (ROS) when compared with baseline. Quercetin highest dose determined dilation in all arteriolar orders (by 40 ± 4 % of baseline in order 2) and prevented microvascular permeability (0.15 ± 0.02 NGL), leukocyte adhesion (3 ± 1/100 µm v.l./30s) as well as ROS formation, while capillary perfusion was protected. Inhibition of endothelial Nitric Oxide Synthase (NOS) prior to quercetin reduced arteriolar dilation (order 2 diameter increase by 10.3 ± 2.5% of baseline) and caused permeability increase (0.29 ± 0.03 NGL); inhibition of neuronal NOS or inducible NOS did not affect quercetin-induced effects. Inhibition of guanylyl cyclase prior to quercetin reversed the quercetin’s effects on pial arteriolar diameter and leakage. In conclusion, quercetin was able to protect pial microcirculation from ischemia-reperfusion damage inducing arteriolar dilation likely by nitric oxide release. Moreover, quercetin scavenger activity blunted reactive oxygen species formation preserving the blood-brain barrier integrity.